PENGARUH KARAKTERISTIK INDIVIDU DAN PEMANFAATAN TEKNOLOGI TERHADAP KINERJA KARYAWAN PADA KANTOR CABANG PT. PELABUHAN INDONESIA IV (Persero) MAKASSAR - Syamsu, Nur; Rahman, Rasyid; Ningrum, Gusti; Huwae, Novelia F; Anggraeni, Yus Rahma (P3M STIEM, 2017)
This research aims to test the influence of Individual Characteristics and utilization Technologyon performance of employees at the branch offices of PT Indonesia Port IV (Persro),Makassar. The Data Collection Uses Primary data that obtained from the questionnaire. Thepopulation was employees of the branch office port of Indonesia IV PT. (Persero) Makassartotalling 164 employees, whereas samples taken just 62 people respondents. The analysisused in hypothesis testing is Statistical package for the Social Sciences (SPSS) version ofIBM SPSS Statistics, 22.0.Results of this research, the individual characteristics of the partially is positive and significanteffect on performance of employees, technology utilization is positive and significant effect onperformance of employees, individual characteristics are dominant variables that have apositive and significant effect on performance of employees